The Reality of Change Leadership among Academic Leaders in Jordanian Private Universities and its Relation to Administrative Creativity - Itmeizeh, Mahmoud; Hassan, Ahdi (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed at finding out the reality of change leadership among academic leaders in Jordanian private universities and its relation to administrative creativity. The descriptive correlational methodology was used. The study sample consisted of (137) faculty members. Two questionnaires were used after assuring their validity and reliability. The results of the study indicated that the reality of change leadership among academic leaders in Jordanian private universities was medium from faculty members’ point of view. The level of administrative creativity of academic leaders in Jordanian private universities was medium too, from faculty members’ point of view. There was a positive significant correlational relationship at (α = 0.01) between the reality of change leadership among academic leaders in Jordanian private universities and the level of administrative creativity of academic leaders. The “r” value was (0.724). Among the recommendations of the study was: Preparing training programs to develop the creative skills of academic leaders.